Penerapan Model Pembelajaran Team Games Tournament (TGT) untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Siswa Kelas V SDN 44 Mataram - Febriani, Jani Febriani; Sukarso, A.A; Wirawan, Mohamad Junaidin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the learning outcomes of fifth-grade students at SDN 44 Mataram in the subject of Pancasila Education through the implementation of the Team Games Tournament (TGT) learning model. This classroom action research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The results showed an increase in the students’ average scores from the pre-cycle to Cycle II. In Cycle I, the average score increased from 62.8 to 74.6 with a classical mastery level of 65%. In Cycle II, the average score reached 85.2 with a classical mastery level of 90%. The TGT learning model proved effective in enhancing student engagement, strengthening material understanding, and fostering a competitive and cooperative learning spirit. Therefore, TGT can be considered a relevant strategy to improve learning outcomes in Pancasila Education at the elementary school level.